(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Innate receptor called toll-like receptor 9 is capable of identifying both microbial and vertebrate DNA.It has been found in both normal mammary gland epithelial cells and breast milk cells.TLR-9was estimated in serum of patients and breast tissue for breast disease. Methods: A 100 women (17–60 years old) were determined undergoing breast surgery at Babylon Province’s Al-Fayhaa Al Ahly Hospital and AL-Hilla Teaching Hospital provided blood and breast tissue samples. Hospital histology lab and clinical surgery performed histological confirmation of breast diseases( benign and malignant tumors). Twenty blood samples were taken as controls from women who appeared to be in good health. TLR9 was measured in the serum of patients with breast diseases as well as the control group using ELIZA. Results: The mean level of TLR9 in serum of patient was 339.4667 ng/l while control was 316.9929 ng/l with found significant differences where P_value was (0.05). while tissue of patient was 276.1064 ng/l. Concentrations of TLR9 were significantly higher in serum compared with tissues at (P≥0.05).The results found no significantly differences in concentrations of TLR9 among types of diseases in sera of patients. This study found concentration of TLR9 increased with primary breast diseases and it might be prognostic marker Conclusion : This study found concentration of TLR 9 increased with primary breast diseases and it might be prognostic marker